Reply to Pitogo et al.: No single silver bullet to simply understand war-biodiversity conflict in the Philippines - Krizler Cejuela. Tanalgo; Bona Abigail Hilario-Husain; Sarrah Jane C. Guerrero; Francisco Gil N. Garcia; Tessie E. Lerios; May Eva Z. Garcia; Renee Jane Alvaro-Ele; Meriam Manampan-Rubio; Sedra A. Murray; Lothy F. Casim; Jamaica L. Delos Reyes; Kier Celestial. Dela Cruz; et al. (npj Biodiversity)
Abstract Sociopolitical conflicts have significant but often overlooked impacts on biodiversity. In our reply, we reaffirm key findings from our previous work and directly address the Matters Arising raised by Pitogo and colleagues. Additionally, we present fine-scale analyses that further support our original conclusions. We emphasise the need for continued research to fully unravel the complex relationship between conflict and environmental impacts.